Mancoa chontaensis, a new species from Peru, and a synopsis of the genus Mancoa (Halimolobeae; Brassicaceae) - Al-Shehbaz, Ihsan A.; Cano, Asunción; Machahua, Miguel; Roque, José; Mazzei, Piero (Phytotaxa, 2025)
The new Peruvian species, Mancoa chontaensis, is described from two localities. It is readily distinguished from its nine congeners by the subangustiseptate siliques instead of strongly angustiseptate silicles. The generic limits is expanded, and a key to all ten species of the genus and their country distributions are presented.